Growth and distributive effects of public infrastructure investments in China - Zhang, Yumei; Wang, Xinxin; Chen, Kevin Z. (2013)
China has recently been spending more than 10 % of total annual government expenditures on public infrastructure. In late 2008, when the global financial crisis occurred, a four trillion yuan package was put into action to stimulate domestic economic growth. Public infrastructure investment in 2009 and 2010 was respectively 60 % and 80 % higher than in 2008. China has managed to sustain rapid economic growth in recent years. However, disparities between rich and poor have risen, and China has become one of the most unequal countries in the world. Despite high overall economic growth rates, the Chinese government is becoming increasingly concerned about high and rising income inequality. Reducing poverty and inequality through inclusive growth has become a major mandate of development policy. President Hu Jintao formally endorsed inclusive growth as a national development strategy at the Asia-Pacific Economic Cooperation (APEC) in November, 2009.